Professional quality of life among physicians posted in COVID-19 clinics at a tertiary care hospital in South India: a cross-sectional analytical study - Rajaa, Sathish; Govindhan, Dhanajayan; Thulasingam, Mahalakshmy (International Journal Of Community Medicine And Public Health, 2023)
Background: COVID-19 pandemic has largely affected the well-being and quality of life among health care workers. We undertook this study to assess the burden and determinants of compassion satisfaction, burnout and Secondary traumatic stress among resident doctors Methods: A cross-sectional analytical study was done among the residents posted in covid wards for clinical duties in tertiary care in Puducherry. All residents who did at least 5 shifts during the last month of their COVID duty were emailed a google form that contained the professional quality of life questionnaire version 5. Results: Around 108 residents agreed to participate in the study. We found that around 80% of the residents experienced moderate compassion satisfaction, while 73% of them experienced moderate burnout, and 66% of them experienced secondary traumatic stress. Speciality, marital status, tobacco use, and being posted in ICU/wards stood out as independent determinants of burnout, while caffeine/ alcohol and tobacco intake were found to be associated with secondary traumatic stress. Conclusions: Thus, our study highlights the burden of burnout among residents posted in COVID wards.